Huge Cutaneous Metastases from Gastric Adenocarcinoma: Report of a Rare Case - Mafi, Ahmad R (Reports of Radiotherapy and Oncology, 2020)
Cutaneous metastases from gastric cancer are quite rare, accounting for only 6% of all skin metastases in males and 1% in females. In case of occurrence, they are usually a sign of advanced disease and poor prognosis. This report presents a rare case of a 27-year-old male with gastric cancer who developed huge skin metastases and surprisingly, had a few visceral metastases. After four cycles of palliative chemotherapy, he discontinued the treatment and started to consume some herbal medicine. As he had a few visceral metastases, we presume that he passed away due to septic complications of the skin lesions rather than visceral crisis.